CD24 Is Not Required for Tumor Initiation and Growth in Murine Breast and Prostate Cancer Models. - Natascha Cremers; Antje Neeb; Tanja Uhle; Arno Dimmler; Melanie Rothley; Heike Allgayer; Riccardo Fodde; Jonathan Paul Sleeman; Wilko Thiele (PLoS ONE)
CD24 is a small, heavily glycosylated, GPI-linked membrane protein, whose expression has been associated with the tumorigenesis and progression of several types of cancer. Here, we studied the expression of CD24 in tumors of MMTV-PyMT, Apc1572/T+ and TRAMP genetic mouse models that spontaneously develop mammary or prostate carcinoma, respectively. We found that CD24 is expressed during tumor development in all three models. In MMTV-PyMT and Apc1572T/+ breast tumors, CD24 was strongly but heterogeneously expressed during early tumorigenesis, but decreased in more advanced stages, and accordingly was increased in poorly differentiated lesions compared with well differentiated lesions. In prostate tumors developing in TRAMP mice, CD24 expression was strong within hyperplastic lesions in comparison with non-hyperplastic regions, and heterogeneous CD24 expression was maintained in advanced prostate carcinomas. To investigate whether CD24 plays a functional role in tumorigenesis in these models, we crossed CD24 deficient mice with MMTV-PyMT, Apc1572T/+ and TRAMP mice, and assessed the influence of CD24 deficiency on tumor onset and tumor burden. We found that mice negative or positive for CD24 did not significantly differ in terms of tumor initiation and burden in the genetic tumor models tested, with the exception of Apc1572T/+ mice, in which lack of CD24 reduced the mammary tumor burden slightly but significantly. Together, our data suggest that while CD24 is distinctively expressed during the early development of murine mammary and prostate tumors, it is not essential for the formation of tumors developing in MMTV-PyMT, Apc1572T/+ and TRAMP mice.